CAMPUR KODE PENYIAR RADIO DI EKS-KARESIDENAN SURAKARTA - Eka Susylowati; Rahmat Wisudawanto (Nusantara Hasana Berdikari, 2021)
The aim of the research to describe the forms of radio broadcaster code mixing in ex-Karesidenan Surakarta. Data collection used by observation, in-depth interviews, and documentation. Meanwhile, data analysis using a contextual approach. The results showed that outer code mixing and inner code mixing. Outer code mixing from Indonesian into English and Korean and inner code mixing into from Indonesian into Javanese. It is influenced by modern technology, to find out the special term, to increase competency of foreign language.